2021
DOI: 10.1186/s12920-021-01016-8
|View full text |Cite
|
Sign up to set email alerts
|

Whether, when, how, and how much? General public’s and cancer patients’ views about the disclosure of genomic secondary findings

Abstract: Background Data on the modalities of disclosing genomic secondary findings (SFs) remain scarce. We explore cancer patients’ and the general public’s perspectives about disclosing genomic SFs and the modalities of such disclosure. Methods Sixty-one cancer patients (n = 29) and members of the public (n = 32) participated in eight focus groups in Montreal and Quebec City, Canada. They were asked to provide their perspectives of five fictitious vignett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The question was not about selecting one or the other mode of disclosure as the optimal approach but rather using a mix of both family-mediated and healthcare-mediated disclosure efforts, preferably with healthcare taking the main responsibility. Wishes for more active collaboration with HCPs has been reported in studies of Canadian cancer patients [28], US patients with hereditary cancer [31] and in patients, relatives and the public in the Netherlands [27]. In our data several constellations and approaches were envisioned.…”
Section: Sharing the Responsibility By Collaboration With Hcpsmentioning
confidence: 82%
See 3 more Smart Citations
“…The question was not about selecting one or the other mode of disclosure as the optimal approach but rather using a mix of both family-mediated and healthcare-mediated disclosure efforts, preferably with healthcare taking the main responsibility. Wishes for more active collaboration with HCPs has been reported in studies of Canadian cancer patients [28], US patients with hereditary cancer [31] and in patients, relatives and the public in the Netherlands [27]. In our data several constellations and approaches were envisioned.…”
Section: Sharing the Responsibility By Collaboration With Hcpsmentioning
confidence: 82%
“…Our respondents clearly solicited easily accessible and concrete risk information with visual aids to make the message understandable to laypeople. Focus group studies from Canada and Australia have also reported wishes for clear, brief and graphically illustrated risk information [28,54]. Besides these wishes, our respondents voiced a clear desire for information to be highly personalized, preferably based on their family situation and to include contact information to easily accessible HCPs.…”
Section: More Personalized Information To Allow Informed Decisionsmentioning
confidence: 87%
See 2 more Smart Citations
“…Actionability of results has long been recognised as a criterion for returning GS results. Previous studies suggest that patients consider results with personal utility (such as for reproductive purposes) to be 'actionable', while researchers typically consider those with clinical utility to be 'actionable' [7,8] and therefore worthy of return [9][10][11]. Research also suggests that a person's preferences may be impacted by psychological factors, such as knowledge, worry about genetic risks [5], having genetically related children [12] and genetic causal beliefs [13], so that healthcare providers and patients may view the same results differently.…”
Section: Introductionmentioning
confidence: 99%